CD8+ T cells mediate ultraviolet A‐induced immunomodulation in a model of extracorporeal photochemotherapy. Issue 5 (10th February 2020) - Hequet, Olivier; Nosbaum, Audrey; Guironnet‐Paquet, Aurélie; Blasco, Elisabeth; Nicolas‐Virelizier, Emmanuelle; Griffith, Thomas S.; Rigal, Dominique; Cognasse, Fabrice; Nicolas, Jean‐François; Vocanson, Marc
Abstract: Extracorporeal photochemotherapy (ECP) that takes advantage of the immunomodulatory effects of UV light has been extensively used for many years for the treatment of several T cell–mediated diseases, including graft‐versus‐host disease (GvHD) and systemic scleroderma. Immune mechanisms that lead to the establishment of T cell tolerance in ECP‐treated patients remain poorly known. In this study, we have tested the effect of UV/psoralen‐treated BM‐derived dendritic cells, referred to as ECP‐BMDCs on the outcome of an antigen‐specific T cell‐mediated reaction, that is, contact hypersensitivity (CHS), which is mediated by CD8 + effector T cells (CD8 + Teff ). The intravenous (i.v.) injection of antigen‐pulsed ECP‐BMDCs in recipient C57BL/6 mice induced specific CD8 + T cells endowed with immunomodulatory properties (referred to as CD8 + TECP ), which prevented the priming of CD8 + Teff and the development of CHS, independently of conventional CD4 + regulatory T cells. CD8 + TECP mediated tolerance by inhibiting the migration and functions of skin DC and subsequently the priming of CD8 + Teff . CD8 + TECP displayed none of the phenotypes of the usual CD8 + T regulatory cells described so far. Our results reveal an underestimated participation of CD8 + T cells to ECP‐induced immunomodulation that could explain the therapeutic effects of ECP in T cell‐mediated diseases. Abstract : Mechanisms of CD8 + TECP –induced immunomodulation: ECP‐treated Ag‐pulsed DCs generates CD8 + TECP (Step 1). Ag‐immunization is performed through the skin (Step 2). CD8 + TECP inhibit the migration and stimulatory functions of skin DCs (Step 3), which hampers the priming of CD8 + Teff (Step 4) and then induces decreased skin inflammation upon challenge (Step 5).